2010
DOI: 10.1074/jbc.m110.183392
|View full text |Cite
|
Sign up to set email alerts
|

Induced Pluripotent Stem Cells Can Be Used to Model the Genomic Imprinting Disorder Prader-Willi Syndrome

Abstract: The recent discovery of induced pluripotent stem cell (iPSC) technology provides an invaluable tool for creating in vitro representations of human genetic conditions. This is particularly relevant for those diseases that lack adequate animal models or where the species comparison is difficult, e.g. imprinting diseases such as the neurogenetic disorder PraderWilli syndrome (PWS). However, recent reports have unveiled transcriptional and functional differences between iPSCs and embryonic stem cells that in cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(59 citation statements)
references
References 47 publications
0
57
0
2
Order By: Relevance
“…However, recent studies have suggested that iPSCs from PWS patients maintained their imprinting pattern even after reprogramming (Chamberlain et al, 2010;Yang et al, 2010). This discrepancy between mouse and human iPSCs may be attributable to differences in the pluripotent state of iPSCs: mouse ESCs and iPSCs appear to be in a developmentally less-advanced pluripotent state than human ESCs and iPSCs.…”
Section: Discussionmentioning
confidence: 86%
“…However, recent studies have suggested that iPSCs from PWS patients maintained their imprinting pattern even after reprogramming (Chamberlain et al, 2010;Yang et al, 2010). This discrepancy between mouse and human iPSCs may be attributable to differences in the pluripotent state of iPSCs: mouse ESCs and iPSCs appear to be in a developmentally less-advanced pluripotent state than human ESCs and iPSCs.…”
Section: Discussionmentioning
confidence: 86%
“…NPC differentiation from hESCs and hiPSCs derived from both SFs and UCs was performed as described previously [26,30,35,36]. The typical neural rosettes were blown off and picked out to produce a neural sphere consisting of Figure 1A).…”
Section: Npc Differentiation From Hescs/hipscsmentioning
confidence: 99%
“…Disease modeling based on iPSC technology has also been applied to many other neurological or psychiatry disorders, including Alzheimer's disease [32] , Huntington's disease [33,34] , Angelman and Prader-Willi syndromes [35,36] , schizophrenia [37] , and others (Table 1).…”
Section: Neurological Diseasesmentioning
confidence: 99%